Associations among immunophenotype, plasma metabolites, and benign prostatic hyperplasia: a mediation Mendelian randomization study - FAN Jiuming; ZHAO Yiqiao; JIA Haichang; WANG Tiankun; HAN Yutong; QIN Zihao; CHEN Ping; ZENG Xiantao (Yixue xinzhi zazhi)
Objective To explore the potential causal relationship between immune cells, plasma metabolites and benign prostatic hyperplasia (BPH) and the mediating role of plasma metabolism by using the mediated Mendelian randomization (MR) method. Methods Two-sample bidirectional MR analysis was used to predict the immune phenotype that may affect BPH, and immune cells that were adversely affected by BPH were excluded. Secondly, one-way two-sample MR analysis was used to screen plasma metabolites associated with BPH and whether they were affected by immune cells were explored. The causal relationship between plasma metabolites and BPH was evaluated by the same method. Finally, the mediating effect of plasma metabolites between immune cells and BPH was further estimated. Results Through bidirectional MR analysis, the study identified significant associations between eight immune cell phenotypes and BPH. IVW analysis revealed that five immune cell phenotypes were protective against BPH, while three phenotypes were significantly associated with increased BPH risk. In the MR analysis of blood metabolites and BPH, IVW results identified 17 blood metabolite markers with significant causal associations with BPH. Among these, eight metabolites were significantly linked to an increased risk of BPH, while nine metabolites were associated with a reduced risk. Mediation MR analysis identified two key causal pathways. The first pathway involves DP[CD4(+)CD8(+)]AC influencing BPH through the 5-methylthioadenosine (MTA) phosphate ratio [mediation proportion=-12.086%, 95%CI(-22.430%, -1.742%)]. The second pathway involves CD19 on IgD(-)CD24(- ) affecting BPH via deoxycholic acid glucuronide levels [mediation proportion=-11.230%, 95%CI(-21.873%, -0.588%)]. Both metabolites showed mediation proportions exceeding 10%, suggesting a significant mediatory role in the relationship between immune cells and BPH.Conclusion This study highlights two distinct immune phenotypes associated with BPH, mediated by specific plasma metabolites through mediation MR analysis. These findings offer novel insights into the pathophysiology of BPH and identify potential biomarkers and therapeutic targets for its diagnosis and management.